Tolerance of platelet concentrates treated with UVC‐light only for pathogen reduction – a phase I clinical trial. Issue 1 (6th March 2015) - Thiele, T.; Pohler, P.; Kohlmann, T.; Sümnig, A.; Aurich, K.; Selleng, K.; Westphal, A.; Bakchoul, T.; Petersmann, A.; Müller, T. H.; Greinacher, A.; Seltsam, A.
<x xml:space="preserve">Abstract</x> Background The THERAFLEX UV‐Platelets pathogen reduction system for platelet concentrates (PCs) operates with ultraviolet C light (UVC; 254 nm) only without addition of photosensitizers. This phase I study evaluated safety and tolerability of autologous UVC‐irradiated PCs in healthy volunteers. Methods Eleven volunteers underwent two single (series 1 and 2) and one double apheresis (series 3). PCs were treated with UVC, stored for 48 h and retransfused in a dose‐escalation scheme: 12·5, 25% and 50% of a PC (series 1); one complete PC (series 2); two PCs (series 3). Platelet counts, fibrinogen, activated partial thromboplastin time, prothrombin time, D‐dimer, standard haematology, temperature, heart rate, blood pressure and clinical chemistry parameters were measured. One‐ and 24‐h corrected count increments were determined in series 2 and 3. Platelet‐specific antibodies were assessed before and at the end of the study. Results Neither adverse reactions related to transfusions nor antibodies against UVC‐treated platelets were observed. Corrected count increments did not differ between series 2 and 3. Conclusions Repeated transfusions of autologous UVC‐treated PCs were well tolerated and did not induce antibody responses in all volunteers studied. EudraCT No. 2010‐023404‐26.